Communication Styles in EFL Classroom Interaction - Jusriati Jusriati; Nasriandi Nasriandi; Puspa Sari (LPPM Universitas Bina Sarana Informatika, 2020)
This research identified types and the dominant communication styles used by a teacher in EFL classroom interaction based on theory of Mikoluk (2013) and Lanz (2015). Descriptive qualitative research method was applied to find out the phenomena of communication styles used by the teacher in EFL classroom interaction. The subject of this research is single participant, a teacher of SMA Negeri 3 Palopo. The participant was chosen by using purposive sampling technique. The researcher observed and interviewed the teacher to reveal the phenomena under investigation. Observation was conducted in six meetings from different context such as different class, time and learning topic. The researcher conducted observation by using audio recorder and field notes. Audio recorder was used to record teacher’s utterance in the teaching and learning process. Meanwhile field notes used by the researcher to obtain more accurate data. Interview was used to know the teacher’s dominant communication styles. The result of this research showed that there were three types of communication styles that used by the teacher in EFL classroom interaction namely aggressive style, assertive style, and passive style and the dominant one was aggressive style.